POZIOM JAKOŚCI DÓBR A ZYSK PRZEDSIĘBIORSTWA - Marczak, Marek (Wydział Prawa i Administracji UAM, 2003)
The article presents a theoretical multifaceted analysis of the relation between the quality level of a product and the income incurred, costs charged and profit achieved by a company. The conclusions drawn from this contemplation are supported by the research results conducted by the Strategic Planning Institute in the USA.
THE LEVEL OF PROPERTY QUALITY VS. PROFIT OF MANUFACTURING BUSINESS